Increasing the involvement of citizens in the decision-making process of territorial development through digitalization - Alisharipov, A.T.; Utepova, G.M.; Kusainova, L.I. (BUKETOV BUSINESS REVIEW, 2024)
Object: The introduction of participatory budgeting in a digital format in order to increase civic engagement in making managerial decisions on territorial development. The hypothesis of the study is that digital participatory budgeting increases the role of institutions of local government and civil society. Methods: The study used the method of content analysis in the study of foreign experience and normative legal acts regulating the activities of local self-government of the Republic of Kazakhstan. Findings: Based on the results of the analysis, it was revealed that the policy of decentralization affects the territorial development of developed countries. The level of decentralization is closely related to how local governments perform their role in the distribution of various functions within the public administration system and is crucial for regional development. In this regard, the project "Organization of a set of measures aimed at the development of local self-government" in Kazakhstan uses a digital platform of participatory budgeting to involve citizens, public organizations, local authorities and local community meetings for the uniform development of the country’s regions. Conclusions: Currently, the Republic of Kazakhstan is in the process of building a new model of interaction between the state apparatus and citizens based on the principle of "human-centricity". The conducted research shows that the use of digital platforms contributes to an increase in the activity of citizens in the process of making managerial decisions. The Berekeli Bastama project, launched at the level of the entire republic, can become a driver for the development of participatory budgeting and the development of the territory as a whole.